Morphological and molecular investigation of freshwater Hildenbrandia (Hildenbrandiales, Rhodophyta) with a new species reported from Japan - Nan, Fang-Ru; Han, Jin-Fen; Feng, Jia; Lv, Jun-Ping; Liu, Qi; Liu, Xu-Dong; Xie, Shu-Lian (Phytotaxa, 2019)
The morphological characterization and phylogenetic analysis based on molecular methods were executed on the freshwater Hildenbrandia specimens collected in this study. The cell size and filament height of the specimen collected from Pipa Lake, Japan were larger than the widely recognized species Hildenbrandia angolensis and Hildenbrandia rivularis, whereas overlapped with Hildenbrandia jigongshanensis. Based on molecular evidences of rbcL phylogenetic analysis and comparison of ITS1 secondary structure, specimen collected from Shiga Prefecture, Japan was proposed as a new species Hildenbrandia japananense. It brings the freshwater Hildenbrandia species in Japan to two. The specimens collected from Niangziguan, Shanxi province, China represent two new records of H. jigongshanensis. It enriches the species diversity of genus Hildenbrandia and increases the distribution diversity of this freshwater red algal taxon.